Literary Modernity in Late Qajar Era Press - Mohammad Reza Haji-Agha Babaie (تاریخ ادبیات)
While literary modernity in Iran had national underpinnings and was brought about by changes in the economic and political relations and infrastructures of the country, it was also influenced by the knowledge of Western literature, and Iranian intellectuals who were producing works of literature also promoted new perspectives and styles in literature through the publication of their works. Examining the publications in the time period starting from the Constitutional Revolution to the end of Qajar era, we found that the issue of literary modernity was present in the following areas: theoretical issues of literary modernity, innovation in the form and content of literary texts, flourishing of translation, development of literary research, and flourishing of literary criticism. However, Iranian intellectuals and scholars had different understandings of modernity. Some believed that modernity was tantamount to destroying tradition and everything belonging to the past, and that it meant moving away from the literary past to create a literature that suited the contemporary times. Another group of modernists who had nationalist tendencies considered the aim of literary modernity to be the purification of Persian language by eliminating Arabic and Western [loan] words. Another group of scholars took the middle ground on the issue of modernity. They believed that new topics could be addressed while preserving the literary tradition. To them, tradition and modernity were not in conflict, but rather were a continuous issue, and modernity could take shape alongside tradition.